Growth Hormone Status In Obese Subjects and Correlation With Age - Mufarrihul Ihsan; Lilik Herawati; Purwo Sri Rejeki (Universitas STRADA Indonesia, 2020)
Obesity also increases the risk of decreased Growth Hormone (GH) secretion. Decreased GH secretions have an impact on increasing body fat and decreasing lean body mass. This study aims to analyze the status of Growth Hormone (GH) in obese subjects and the correlation of GH with age. This study used a cross sectional study method using 30 obese female adolescent Body Mass Index (BMI) subjects 25-35 kg/m2, Percentage of Body Fat (PBF) above 30% and fasting blood glucose (FBG) below 100 mg/dL. Measurement of GH levels used the Enzym Link Immunosorbent Assay (ELISA) method. Data analysis techniques used the Pearson Correlation test with the Statistical Package for Social Science. Results obtained mean GH levels (761.119±504.627) pg/mL and average age (20.863±1.082) years (r =-0.483) and (p=0.023). Based on the results of the study, it can be concluded that there is a negative correlation between GH status and age in obese subjects